Managing youth work - Tyler, Mary; Hoggarth, Liz.; Merton, Bryan (Exeter Learning Matters, 2009)
This work ensures that students will feel confident to manage purpose, projects and people and to deliver good quality educational and developmental youth work with and for young people.
Keywords: Youth -- Services for -- Management; Social work with youth -- Management